Individual differences in the neuroendocrine response of male rats to emotional stressors are not trait-like and strongly depend on the intensity of the stressors. (March 2021) - Nadal, Roser; Gabriel-Salazar, Marina; Sanchís-Ollé, María; Gagliano, Humberto; Belda, Xavier; Armario, Antonio
Abstract: Biological response to stressors is critical to understand stress-related pathologies and vulnerability to psychiatric diseases. It is assumed that we can identify trait-like characteristics in biological responsiveness by testing subjects in a particular stressful situation, but there is scarce information on this issue. We then studied, in a normal outbred population of adult male rats (n = 32), the response of well-characterized stress markers (ACTH, corticosterone and prolactin) to different types of stressors: two novel environments (open-field, OF1 and OF2), an elevated platform (EP), forced swim (SWIM) and immobilization (IMO). Based on both plasma ACTH and prolactin levels, the OF1 was the lowest intensity situation, followed by the OF2 and the EP, then SWIM and finally IMO. When correlations between the individual responses to the different stressors were studied, the magnitude of the correlations was most dependent on the similarities in intensity rather than on other characteristics of stressors, with good correlations between similar intensity stressors and no correlations at all were found between stressors markedly differing in intensity. In two additional confirmatory experiments (n = 37 and n = 20) with HPA hormones, we observed good correlation between the response to restraint and IMO, which were close in intensity, and no correlation between OF1 and SWIM. The present results suggest that individual neuroendocrine response to a particular stressor does not predict the response to another stressor greatly differing in intensity, thus precluding characterization of low or high responsive individuals to any stressor in a normal population. The present data have important implications for human studies. Highlights: ACTH and prolactin are good markers of stressor intensity. Correlation of hormonal response decreases when stressors differ in intensity. A phenotype of low or high reactivity to stress cannot be defined.